Analysis of stochastic acoustical hazards in environment - Batko, Wojciech; Bal-Pyrcz, Renata (Archives of Acoustics, 2007)
Acoustical assessment of environment, realized on the basis of changes observation heldas part of national environment monitoring for the need of long term noise protection policyin environment, demands long term average noise level $L_{DEN}$ and $L_{N}$ estimation. Theestimation is based on noise measurement results from all the days in the year, taking into accountday, evening and night times. The basis for correct statistical estimation when the datais incomplete (time limited monitoring of acoustic environment) is a choice of time sample sothat results gained reflect the mechanism of noise hazard changes that works throughout theyear. It should provide identification of particular event occurring frequency and time relationsbetween events, e.g. sound extreme value appearance or recognition of periodical changes ofimportant parameters in uncertainty assessment. Such process demands assumption of particularstatistical techniques related to the assumed model of noise level changes where therandom factor is important and always present. That problem is part of the article. The paperpresents basic analysis of monitored phenomenon by usage of models framing its stochasticvolatility. Important elements of modeling are described, illustrated by examples of yearlynoise data analysis gathered at one of main streets in Kraków. Attention is paid to the analysisproblem with the process periodicity, measurement uncertainty related to the measurementconditions volatility or time uniformity of the monitored noise processes in view of its internalcausality relations.They are loaded with random factor whether we assign randomness to noise source volatility,whole year measurement conduct inability or distortions related to proper sampling ofgiven field of noise hazards.